Effect of Coarse Wheat Bran and Crude Protein Level in Nursery Pig Diets Without Pharmacological Levels of Zinc Oxide - K. L. Batson; H. I. Calderón; M. D. Tokach; J. C. Woodworth; R. D. Goodband; S. S. Dritz; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 360 pigs (200 × 400; DNA, Columbus, NE, initially = 12.4 lb) were used in a 45-d growth trial to evaluate the effects of coarse wheat bran and crude protein level in diets without pharmacological levels of zinc oxide (ZnO) on growth performance of nursery pigs. Upon arrival to the nursery research facility, pigs were randomly assigned to pens with 5 pigs per pen. Pens were allotted to 1 of 6 dietary treatments in a completely randomized design with 12 pens per treatment. Treatment diets were offered in two dietary phases (phase 1 fed from d 0 to 7, and phase 2 from d 7 to 21 post-weaning). A post-treatment period with a common diet was fed from d 21 to 45. Treatment diets included a positive control diet with pharmacological ZnO (3,000 ppm Zn in phase 1 and 2,000 ppm in phase 2); negative control without pharmacological ZnO (110 ppm Zn added from premix); and negative control with 4% coarse wheat bran and formulated to contain 21, 19.5, 18, or 16.5% crude protein (CP). The two control diets and the 21% CP diet contained 1.40% standardized ileal digestible (SID) lysine in phase 1 and 1.35% SID lysine in phase 2, with the 19.5, 18, and 16.5% CP diets containing 1.33, 1.25 and 1.20% lysine, respectively in both phases. Fecal samples were collected from the same three pigs per pen on d 7, 14, 21, and 45 then pooled within pen for each day of collection and dried at 55°C in a forced air oven. All pens were individually scored on d 7, 14, 21, and 45 by the same three individuals to determine visual fecal consistency. Data were analyzed using the lmer function from the lme4 package in R. From d 0 to 21, pigs fed the positive control diet containing ZnO had increased (P<0.001) average daily gain (ADG) and average daily feed intake (ADFI) and improved (P<0.050) feed efficiency (F/G) compared to the negative control and the high CP coarse wheat bran diet. Reducing crude protein levels in diets containing coarse wheat bran resulted in decreased ADG and poorer feed efficiency (linear,P= 0.002); however, fecal dry matter percentage was increased (linear,P= 0.006), suggesting a greater occurrence of solid feces throughout the experimental period. Overall from d 0 to 45, decreasing crude protein level decreased (linear,P= 0.012) ADG, ADFI (linear,P= 0.038), and d 45 body weight (linear,P= 0.010). Pigs fed the positive control diet with ZnO experienced increased ADG (P= 0.014) and increased ADFI (P= 0.008) compared to the negative control. There was no evidence for differences in overall growth for the positive control compared with the 21% CP diet with coarse wheat bran. In summary, decreasing crude protein in diets with coarse wheat bran decreased overall ADG and ADFI, resulting in lower body weight throughout the study. The pigs fed these diets had poorer feed efficiency and decreased ADG during the experimental period; however, these pigs had increased fecal dry matter. Further research is warranted to determine if low crude protein diets can be modified to achieve increased fecal dry matter while maintaining growth performance of nursery pigs.
Keywords: crude protein; fecal dry matter; nursery pig; wheat bran; zinc oxide